International Students by Treaty: Common Space, Different Vulnerabilities - Smart, Cherry-Ann (Journal of International Students, 2022)
Nonnational students in the Anglophone Caribbean are often affected by natural or man-made disasters that affect their experiences in the host country. However, the region had never experienced pandemic disasters such as COVID-19. Its occurrence highlighted latent concerns such as prejudices, border issues, and weak institutional support despite the existence of geopolitical treaties. Using the concept of the looming vulnerability framework, and incorporating a transformative lens, the research examined factors that contributed to these students’ vulnerabilities at institutions of higher education in the Caribbean during the pandemic. A qualitative research design using regional newspapers accounted for students’ collective voices. The results showed that nonnational students’ mental well-being was affected by factors including institutional role, management of communication, access to resources, their governments’ expression of financial support, and perceived discrimination from the host community. The article highlights the potential for students’ further marginalization in the absence of pragmatic disaster preparedness plans.